The Indefectibility of the Apostolic See: The Nature and Scope of Divine Assistance for the Ordinary Exercise of the Papal Magisterium - O'Regan, Emmett (Trinity College Dublin. School of Religion. Discipline of Religions and Theology, 2025)
Due to several controversies which unfolded during the pontificate of Pope Francis, a number of Catholic theologians reignited a debate concerning the possibility of a pope teaching heresy via the ordinary exercise of the papal magisterium. The potential of a publicly heretical pope was frequently discussed by theologians and canonists until the seventeenth century, before being rejected by notable figures such as St. Robert Bellarmine and Francisco Suárez. Bellarmine predicated the doctrine of papal infallibility on an earlier tradition dating back to the period of the Early Church, which attested to the indefectible nature of the See of Rome. After the convocation of the First Vatican Council in 1868, the question of papal heresy resurfaced as the major argument against the proposed definition of papal infallibility. The minority bishops at the Council, who were opposed to the solemn definition of papal infallibility, realised that the Deputation on Faith was heavily reliant on Bellarmine's arguments during the drafting stages of Pastor aeternus. Consequently, several leading figures of the anti-infallibilist movement, such as Ignaz von Dllinger and Bishop Karl Josef von Hefele, highlighted the case of Pope Honorius as their major objection against the definition of papal infallibility. As the locus classicus of a heretical pope, Honorius was a source of controversy for the proponents of papal infallibility, since he was condemned for supporting the Monothelite heresy at the Third Council of Constantinople in 681. By examining the official relatio of the conciliar documents, this thesis demonstrates how the majority bishops of the First Vatican Council rejected the possibility of a publicly heretical pope. It goes on to demonstrate that this theological position, which witnesses to the perpetual orthodoxy of the Petrine See, provided the basis for the assent of religious submission to the non-infallible teachings of the ordinary magisterium, which has been proposed as binding in conscience by the Second Vatican Council.
APPROVED
Keywords: Indefectibility; Papal infallibility; St Robert Bellarmine; First Vatican Council; papal heresy; obsequium religiosum; Gallicanism; Ultramontanism